Association of systemic diseases with sudden sensorineural hearing loss - Nepal, MK; Rayamajhi, P; Thapa, N; Bhattarai, H; Shrivastav, RP (Journal of Institute of Medicine Nepal, 2008)
Background: To find out the association of systemic diseases with sudden sensorineural hearing loss and to observe the effect of high dose intravenous steroid in its management. Methods: All patients admitted with sudden sensorineural hearing loss in the department of ENT & Head and Neck Surgery, T. U. Teaching hospital from January 2002 to January 2005 were studied prospectively. Association with any systemic illnesses were noted. High dose steroid intravenously was given for treatment and hearing improvement was assessed by pure tone audiometry. Results: A total of 46 patients were enrolled in the study, 21 of whom had systemic diseases. Predominant systemic disease was diabetes mellitus which was present in 16 patients. After steroid therapy, 13 patient is hearing returned to normal, 13 had improvement in hearing, 16 had no improvement and 4 had their hearing deteriorated. Conclusion: Approximately 45.7% of the patients with sudden sensorineural hearing loss had associated systemic diseases. Only 28.3% of the patient recovered to normal hearing though another 28.3% had improvement in hearing after the high dose steroid therapy. Keywords: Sudden sensorineural hearing loss (SSNHL), pure tone audiometry (PTA), Diabetes mellitus The full text of this paper is available at Journal of Institute of Medicine website